2015
DOI: 10.3892/etm.2015.2840
|View full text |Cite
|
Sign up to set email alerts
|

Cell sheet-engineered bones used for the reconstruction of mandibular defects in an animal model

Abstract: Abstract. The aim of the present study was to investigate the generation of cell sheet-engineered bones used for the reconstruction of mandibular defects. Bone marrow stem cells (BMSCs) were cultured and induced to generate osteoblasts. Poly(lactic-co-glycolic acid) (PLGA) scaffolds were wrapped with or without cell sheets and then implanted into dogs with mandibular defects in the right side (experimental group) or the left side (control group), respectively. Subsequently, X-ray analyses, and hematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The expression of Oct4 was detected over the cell sheets, confirming the preservation of the cell's stemness [32][33][34]. The time for harvesting will vary based on the type of seeded cells (bone marrow cells, dental pulp stem cells, oral mucosal epithelial cells, induced pluripotent stem cells [35][36][37][38], myocardiac cell sheet, osteoblast cell sheet, epithelial cell sheet [11,39,40]), the nature of the culture media, the rate of differentiation, and the formation of the stratified cells sheets. We decided to use the different levels of transparency of engineered cell sheet with adipose derived cells to develop a device that will measure the transmittance of light through the cell sheets.…”
Section: Discussionmentioning
confidence: 70%
“…The expression of Oct4 was detected over the cell sheets, confirming the preservation of the cell's stemness [32][33][34]. The time for harvesting will vary based on the type of seeded cells (bone marrow cells, dental pulp stem cells, oral mucosal epithelial cells, induced pluripotent stem cells [35][36][37][38], myocardiac cell sheet, osteoblast cell sheet, epithelial cell sheet [11,39,40]), the nature of the culture media, the rate of differentiation, and the formation of the stratified cells sheets. We decided to use the different levels of transparency of engineered cell sheet with adipose derived cells to develop a device that will measure the transmittance of light through the cell sheets.…”
Section: Discussionmentioning
confidence: 70%
“…Inducing a concomitant differentiation into osteoblasts while promoting ECM mineralization in this system is innovative. Our osteogenic cell sheet production process is simple and reproducible and does not require modifying or pretreating the culture support, exogenous biomaterials, or supplemental recombinant growth factor treatment . The quality of the osseous cell sheets generated in this study is supported by the measured functional outcomes, which demonstrated robust osteogenic characteristics compared to stromal cell sheets.…”
Section: Discussionmentioning
confidence: 73%
“…Cell sheet technology provides an effective strategy for using BMSCs, not only to minimize the destruction of the ECM, but also to improve cell retention at the transplant site and attachment to the scaffold . BMSC sheets wrapped around a scaffold showed more pronounced capacity for bone regeneration than did cells dispersed in the scaffold …”
Section: Introductionmentioning
confidence: 99%